2010
DOI: 10.1111/j.1939-1676.2009.0464.x
|View full text |Cite
|
Sign up to set email alerts
|

Serological Survey of Bluetongue Virus Serotype-8 Infection in South American Camelids in Switzerland (2007-2008)

Abstract: Background: Outbreak of bluetongue virus serotype-8 (BTV-8) infection in domestic ruminants in Northern Europe. Objective: To investigate the South American camelids' (SAC) susceptibility to BTV-8 infection, their role in the epidemiology of the disease, and the use of currently available serological screening tests in SAC in an endemic region.Animals: Three hundred and fifty-four unvaccinated and 27 vaccinated SAC (170 llamas, 201 alpacas), ranging in age from 1 month to 17 years between June and August 2008.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Such an evidence argues for host-dependent potential of each of the BTV serotypes simply because, compared to other serotypes such as 4, 6, 8, 11, 14 and 16, a previous study observed an increased incidence of serotype 1 in camels (Drif et al, 2018). Though camels is generally conceived to be a non-susceptible host for BTV in the past, experimental investigations have suggested otherwise, where, particularly for serotype 1 and 8, a low rate of replication or infection along with development of neutralizing antibodies have been evidenced and therefore may serve as potential source of infection for susceptible hosts living in close proximity (Zanolari et al, 2010;Batten et al, 2011;Schulz et al, 2012). Thus, routine BT surveillance in camels should be conducted in disease endemic region/s in order to elucidate disease epidemiology and future interventions for its control.…”
Section: Discussionmentioning
confidence: 99%
“…Such an evidence argues for host-dependent potential of each of the BTV serotypes simply because, compared to other serotypes such as 4, 6, 8, 11, 14 and 16, a previous study observed an increased incidence of serotype 1 in camels (Drif et al, 2018). Though camels is generally conceived to be a non-susceptible host for BTV in the past, experimental investigations have suggested otherwise, where, particularly for serotype 1 and 8, a low rate of replication or infection along with development of neutralizing antibodies have been evidenced and therefore may serve as potential source of infection for susceptible hosts living in close proximity (Zanolari et al, 2010;Batten et al, 2011;Schulz et al, 2012). Thus, routine BT surveillance in camels should be conducted in disease endemic region/s in order to elucidate disease epidemiology and future interventions for its control.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies against BTV‐8 were determined with the Bluetongue Virus Antibody Test kit e , 14 . This cELISA was performed according to the manufacturers' recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…8,18 Conflicting findings were reported in Switzerland where a serological survey indicated that exposed animals were serologically negative by competitive enzymelinked immunosorbent assay, suggesting that New World camelids had not played an important role in BTV-8 spread since 2007. 27 There is however little information regarding the impact of different BTV serotypes, as well as different arthropod vectors, on the manifestation and susceptibility of New World camelids to BT exposure and infection.…”
Section: Brief Research Reportsmentioning
confidence: 99%